2022
DOI: 10.1155/2022/3730679
|View full text |Cite
|
Sign up to set email alerts
|

The Predicting Role of Serum TSGF and sIL-2R for the Lymph Node Metastasis of Papillary Thyroid Carcinoma

Abstract: Objective. To explore the clinical utility of tumor-specific growth factor (TSGF) and the soluble interleukin-2 (IL-2) receptor (sIL-2R) as immune-related factors for predicting lymph node metastases (LNM) of papillary thyroid carcinoma (PTC). Methods. A total of 206 patients with PTC subjected to curative surgery were enrolled. All patients had complete medical records. Serum levels of TSGF were detected using Automatic Biochemistry Analyzer and the serum sIL-2R concentration was detected by enzyme-linked imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…The results of this study demonstrated that TSH suppression therapy could reduce the level of CD44V6 in serum, thus reducing the tumor recurrence and metastasis rates of TC cells after surgery, which was conducive to improving the prognosis. TSGF, also known as a malignant tumor-specific growth factor, is a novel tumor marker whose performance is closely associated with malignant tumor angiogenesis[ 30 , 31 ]. In this study, we also found that TSGF levels were significantly lower in TC patients after TSH suppression therapy, which further proved the therapeutic effect of TSH suppression therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study demonstrated that TSH suppression therapy could reduce the level of CD44V6 in serum, thus reducing the tumor recurrence and metastasis rates of TC cells after surgery, which was conducive to improving the prognosis. TSGF, also known as a malignant tumor-specific growth factor, is a novel tumor marker whose performance is closely associated with malignant tumor angiogenesis[ 30 , 31 ]. In this study, we also found that TSGF levels were significantly lower in TC patients after TSH suppression therapy, which further proved the therapeutic effect of TSH suppression therapy.…”
Section: Discussionmentioning
confidence: 99%
“…TSGF levels have been related to tumor differentiation in pancreatic cancer [ 8 ] and lymph node involvement in colon cancer [ 9 ]. Our previous study revealed that increased serum TSGF may enhance the emergence of multifocality and the development of PTC, suggesting that TSGF may be qualified as an excellent promising marker for predicting lymphatic involvement in PTC [ 25 ]. Our results focused on the clinical utility of TSGF in cancer.…”
Section: Discussionmentioning
confidence: 99%